2017
DOI: 10.1186/s11671-016-1771-4
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Circular Photon Drag Effect in the Ag/Pd Nanocomposite

Abstract: We report on the observation of the helicity-dependent photoresponse of the 20-μm-thick silver–palladium (Ag/Pd) nanocomposite films. In the experiment, 120 fs pulses of Ti:S laser induced in the film an electric current perpendicular to the incidence plane. The photoinduced current is a linear function of the incident beam power, and its sign depends on the beam polarization and angle of incidence. In particular, the current is zero for the p- and s-polarized beams, while its sign is opposite for the right- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…According to our results, presented in ref. the CPC generated in the investigated Ag/Pd films is consistent with the circular PDE theory. CPGE does not occur in Ag/Pd films, because Ag/Pd films consist of non‐gyrotropic nanocrystallites of Ag‐Pd solid solution and PdO .…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…According to our results, presented in ref. the CPC generated in the investigated Ag/Pd films is consistent with the circular PDE theory. CPGE does not occur in Ag/Pd films, because Ag/Pd films consist of non‐gyrotropic nanocrystallites of Ag‐Pd solid solution and PdO .…”
Section: Introductionsupporting
confidence: 86%
“…In refs. , we have shown that the photocurrent in Ag/Pd nanocomposite is generated due to PDE and SPGE. This conclusion was based on the obtained angular and polarization dependencies characteristic to PDE and SPGE.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations